Circulation conservation in the outflow of warm conveyor belts and consequences for Rossby wave evolution. (2nd September 2021) - Saffin, Leo; Methven, John; Bland, Jake; Harvey, Ben; Sanchez, Claudio
Abstract: Rossby waves on the jet stream are associated with meridional motions, displacing air and the strong potential vorticity (PV) gradient on isentropic surfaces. Poleward motion along sloping isentropic surfaces typically results in ascent and a ridge of air with low PV values. Latent heating in the ascending warm conveyor belt (WCB) enables air to cross isentropic surfaces so that the WCB outflow into a ridge occurs in a higher isentropic layer than the inflow. However, the PV impermeability theorem states that there can be no PV flux across isentropic surfaces, so how can heating alter the PV pattern of a Rossby wave? Here, the ways in which heating in WCBs can influence Rossby wave evolution at tropopause level are explained in the context of the PV impermeability theorem. First, a WCB outflow volume is defined by the upper tropospheric air in a ridge that has experienced net heating over the last few days, using a tracer within short global model forecasts. Second, the boundary of this outflow volume is tracked backwards using isentropic trajectories allowing quantification of the degree to which circulation is conserved, as predicted by theory, even though the WCB transports mass into the volume from lower isentropic layers. This diabatic flux of mass into the outflow volume results in an increase in density and expansion in the outflow area, the partition being determined approximately by PV inversion. The area expansion, combined with conservation of circulation, implies stronger anticyclonic vorticity. The relative vorticity change from divergent outflow can be as large as the decrease relative to the background planetary vorticity associated with poleward displacement of the circuit. The additional anticyclonic relative motion results in enhanced anticyclonic overturning of PV contours on the eastern flank of the ridge, altering qualitatively the nonlinear evolution of the Rossby wave. Abstract : Isentropic and 3D trajectories are used to investigate the transport of mass into the outflow of warm conveyor belts. Circulation is approximately conserved in the outflow while the mass increases. The increase in anticyclonic vorticity due the resulting expansion of outflow area is comparable to changes due to meridional displacement and alters the Rossby wave pattern.